Continuous Renal Replacement Therapy With oXiris Filter May Not be an Effective Resolution to Alleviate Cytokine Release Syndrome in Non-AKI Patients With Severe and Critical COVID-19 - Kang, Kai; Luo, Yunpeng; Gao, Yang; Zhang, Jiannan; Wang, Changsong; Fei, Dongsheng; Yang, Wei; Meng, Xianglin; Ye, Ming; Gao, Yan; Liu, Haitao; Du, Xue; et al. (Frontiers in Pharmacology, 2022)
In this study, we aimed to determine whether continuous renal replacement therapy (CRRT) with oXiris filter may alleviate cytokine release syndrome (CRS) in non-AKI patients with severe and critical coronavirus disease 2019 (COVID-19). A total of 17 non-AKI patients with severe and critical COVID-19 treated between February 14 and March 26, 2020 were included and randomly divided into intervention group and control group according to the random number table. Patients in the intervention group immediately received CRRT with oXiris filter plus conventional treatment, while those in the control group only received conventional treatment. Demographic data were collected and collated at admission. During ICU hospitalization, the concentrations of circulating cytokines and inflammatory chemokines, including IL-2, IL-4, IL-6, IL-10, TNF-α, and IFN-γ, were quantitatively measured daily to reflect the degree of CRS induced by SARS-CoV-2 infection. Clinical data, including white blood cell count (WBC), neutrophil proportion (NEUT%), lymphocyte count (LYMPH), lymphocyte percentage (LYM%), platelet (PLT), C-reaction protein (CRP), high sensitivity C-reactive protein (hs-CRP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TB), albumin (ALB), serum creatinine (SCr), D-Dimer, fibrinogen (FIB), IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ, number of hospital days and sequential organ failure assessment (SOFA) score were obtained and collated from medical records during hospitalization, and then compared between the two groups. Age, and SCr significantly differed between the two groups. Besides the IL-2 concentration that was significantly lower on day 2 than that on day 1 in the intervention group, and the IL-6 concentrations that were significantly higher on day 1, and day 2 in the intervention group compared to the control group, similar to the IL-10 concentration on day 5, there were no significant differences between the two groups. To sum up, CRRT with oXiris filter may not effectively alleviate CRS in non-AKI patients with severe and critical COVID-19. Thus, its application in these patients should be considered with caution to avoid increasing the unnecessary burden on society and individuals and making the already overwhelmed medical system even more strained (IRB number: IRB-AF/SC-04).